Clinical Relevance of Troponin T Profile Following Cardiac Surgery - Tevaearai Stahel, Hendrik T.; Do, Peter D.; Klaus, Jeremias Bendicht; Gahl, Brigitta; Locca, Didier; Göber, Volkhard; Carrel, Thierry P. (Frontiers in Cardiovascular Medicine, 2018)
Background: Peak post-operative cardiac troponin T (cTnT) independently predicts mid- and long-term outcome of cardiac surgery patients. A few studies however have reported two peaks of cTnT over the first 48–72 h following myocardial reperfusion. The aim of the current study was to better understand underlying reasons of these different cTnT profiles and their possible relevance in terms of clinical outcome. Methods: All consecutive adult cardiac surgical procedures performed with an extra-corporeal circulation during a >6 years period were retrospectively evaluated. Patients with a myocardial infarction (MI) < 8 days were excluded. cTnT profile of patients with at least one value ≥1 ng/mL value were categorized according to the time occurrence of the peak value. Univariable and multivariable analysis were performed to identify factors influencing early vs. late increase of cTnT values, and to verify the correlation of early vs. late increase with clinical outcome. Results: Data of 5,146 patients were retrieved from our prospectively managed registry. From 953 with at least one cTnT value ≥1 ng/mL, peak occurred ≤ 6 h (n = 22), >6 to ≤ 12 h (n = 366), >12 to ≤ 18 h (n = 176), >18 to ≤ 24 h (171), >24 h (218). Age (OR: 1.023; CI: 1.016–1.030) and isolated CABG (OR: 1.779; CI: 1.114–2.839) were independent predictors of a late increase of cTnT over a limit of 1 ng/ml (p < 0.05), whereas isolated valve procedures (OR: 0.685; CI: 0.471–0.998) and cross-clamp duration (OR: 0.993; CI: 0.990–0.997) independently predicted an early elevation (p < 0.05). Delayed elevation as opposed to early elevation correlated with a higher rate of post-operative complications including MI (19.8 vs. 7.2%), new renal insufficiency (16.3 vs. 6.7%), MACCE (32.0 vs. 15.5%), or death (7.4 vs. 4.4%). Conclusion: Profile of cTnT elevation following cardiac surgery depends on patients' intrinsic factors, type of surgery and duration of cross-clamp time. Delayed increase is of higher clinically relevance than prompt post-operative elevation.